SATELLITE IMAGE MAP - NORTHERN FOOTHILLS AND INEXPRESSIBLE ISLAND (VICTORIA LAND, ANTARCTICA), 1:50,000 - FREZZOTTI M.; VITTUARI L.; GRIGIONI P.; DE SILVESTRI L.; SALVATORE, Maria Cristina (Terra Antartica Publication, Siena, 2000)
Here we describe the tecnique used to realised the satellite image map of the Northern Foothills and Inexpressible Island (Antarctica), a huge area around the Italian Scientific Station in Terra Nova Bay (Antarctica).The map details an area of coast hills on the nW side of Terra Nova Bay, that lies to east of the Browning Pass and the Nansen Ice Sheet. The map covers an area of 850 km. The satellite image map has been made by digital integration of a SPOT XS Multi spectral image mosaic and stereo-compilation reduction of TMA airial photograps.